The military occupational stress response scale: Development, reliability, and validity - Wu, Qianwen; Yang, Zhibing; Qiu, Rui; Cheng, Sizhe; Zhu, Xia; Han, Zheyi; Xiao, Wei (Frontiers in Psychology, 2023)
Soldiers in the military are exposed to numerous stressors, including some that are of an extreme nature. The main objective of this military psychology research study was to evaluate soldiers' occupational stress. Even though several tools have been developed to measure stress in this population, to date, none have focused on occupational stress. Hence, we developed the Military Occupational Stress Response Scale (MOSRS) to provide a tool to objectively measure soldiers' occupational stress responses. An initial pool of 27 items was assembled from the literature, existing instruments, and interviews with soldiers. Of those 27, 17 were included in the MOSRS. The scale was subsequently completed by soldiers from one military region, and exploratory factor analysis (EFA) and confirmatory factor analysis were conducted using Mplus8.3 and IBM SPSS 28.0 software, respectively. A total of 847 officers and soldiers were selected for scale testing, and 670 subjects were retained after data cleaning and screening according to the set criteria. After performing the Kaiser–Meyer–Olkin (KMO) and Bartlett's test, principal components analysis (PCA) was appropriate. The PCA yielded a three-factor model (physiological, psychological, and behavioral responses) with the items and factors strongly correlated. The confirmatory factor analysis revealed loads ranging from between 0.499 and 0.878 for each item. The Cronbach's α coefficient of the MOSRS was between 0.710 and 0.900, and the Omega reliability was between 0.714 and 0.898, which were all higher than the critical standard value of 0.7, indicating that the scale has good reliability. Analysis of the discrimination validity of each dimension revealed that the scale has good discrimination validity. The MOSRS demonstrated sound psychometric characteristics with acceptable reliability and validity, suggesting that it could be used to assess occupational stress in military personnel.